Direct additive manufacturing as spring of new tool steels - Cruz, Francisco R. (2023)
Additive manufacturing (AM) is now common in production of metallic matrixes with/ without reinforcements (nanoprecipitates) to improve functional and structural mechanical properties of 3D objects. The presence of liquid phase in direct processes allows the possibility to change the conventional chemical composition of materials homogeneously. Powder Bed Fusion (PBF), in which the high nonequilibrium solidification nature resembles a localized high cooling rate but allowing, still the formation nanocarbides in-situ. Thus, it will be the suitable technology to tailor novel functionally gradient metallic materials. Nevertheless, this character is only present in the upper layers due to the shaping being made layer by layer. During shaping, the previous layers undergo post heat treatments contributing for growing the carbide dimension. Hence, metallic alloys can be developed simultaneously with the processing stage by changing the chemical composition by addition of fundamental elements to the matrix powder. In tool steel the improvement of hardening carbide content can contribute to a better performance concerning hardness and abrasion wear resistance. The present study concerns the addition of vanadium powder and allotropes of carbon, in correlation with the partition coefficient between vanadium and carbon in the steel selected - AISI H13, processed by selective laser melting (PBF/SLM), without requiring adjusting the processing parameters. The hardness attained is analogous to high speed steels, since this allows layers with a similar matrix to the wrought tool steel but with higher content of hardening carbide (VxCy). The sustainability of the final product is evident.